2010
DOI: 10.1002/jor.21095
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin‐6‐sulfate incorporation and mechanical stimulation increase MSC‐collagen sponge construct stiffness

Abstract: Using functional tissue engineering principles, our laboratory has produced tendon repair tissue which matches the normal patellar tendon force-displacement curve up to 32% of failure. This repair tissue will need to withstand more strenuous activities, which can reach or even exceed 40% of failure force. To improve the linear stiffness of our tissue engineered constructs (TECs) and tissue engineered repairs, our lab is incorporating the glycosaminoglycan chondroitin-6-sulfate (C6S) into a type I collagen scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…36 However, raw material strategies using collagen type II to mimic the native ECM have been employed by other groups with similar success. 22,53,61 Contrasting data were obtained in a study by Ng et al, 32 where no difference was found between the effects of collagen type I and type II gels on mesenchymal stem cell proliferation and contraction. It is important to note, however, that differences in cell type, seeding density, seeding technique, and crosslinking method could all contribute to the discrepancy between these studies.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…36 However, raw material strategies using collagen type II to mimic the native ECM have been employed by other groups with similar success. 22,53,61 Contrasting data were obtained in a study by Ng et al, 32 where no difference was found between the effects of collagen type I and type II gels on mesenchymal stem cell proliferation and contraction. It is important to note, however, that differences in cell type, seeding density, seeding technique, and crosslinking method could all contribute to the discrepancy between these studies.…”
Section: Discussionmentioning
confidence: 79%
“…While most researchers tend to utilize raw materials that are present in the native ECM, cartilage tissue engineering solutions tend to conflict between the selection of type I and type II collagen (Table 3). Several raw material approaches utilize collagen type I to regenerate articular cartilage, 26,28,31,33,37,45,53,56,78 despite the well-known fact that the collagen of hyaline cartilage is predominately type II rather than type I. Studies by Berendsen et al 36 and Ng et al 32 attempted to address this raw material debate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these disadvantages, more researchers have turned their focus on exploring natural biomaterials. [19][20][21]37,[51][52][53][54] Being the main component of native tendon, collagen type I is the most obvious choice of material. Although the biocompatibility is excellent, the poor mechanical properties of reconstituted type I collagen scaffolds has limited their further development as a load-bearing material.…”
Section: Introductionmentioning
confidence: 99%